Re-Conceptualizing the North: A Historiographic Discussion - Martin-Nielsen, Janet (Journal of Northern Studies, 2015)
The past few years have brought a surge in re-conceptualizations of the North in the humanities and social sciences. Bringing together history, environment, geography, politics and culture, these re-conceptualizations offer frameworks, terminology and perspectives designed to situate the North in its complex modern context. They are linked by the authors’ shared interest in what the North has looked like and what it will look like in the future. This paper engages with a few of these re-conceptualizations in order to understand what agendas they put forward, explicitly and implicitly, and how they are situated within historical contexts. In this context, I ask what the North encompasses: which narratives, identities and connections merge with latitude, climate and physical environment to create new (and not-so-new) ways of thinking about northern spaces? Ultimately, I argue that these re-conceptualizations of the North are in fact themselves articulations of the future: developed and presented to tell particular stories, they are part of a larger story, one that reaches into the past and one which will continue to evolve and change.